(untitled) (Ithaca, NY, 1991)
The process of economic development depends on the modernization of agriculture. Agriculture and the State responds to this historical lesson by examining government interventions into the agricultural economy of developing countries. In this attempt to understand the appropriate role of policy, the authors seek to explain government successes and failures in facilitating the contribution of agriculture to the overall development process. The book is the joint effort of eleven scholars and policy analysts of agricultural development from the United States, Europe, Latin America, and Asia
Keywords: Agriculture and state,Agricultural laborers,Rural poor; Developing countries,Congresses,Developing countries,Congresses,Developing countries,Congresses